Production of α-amilase by solid state fermentation by Rhizopus oryzae - Ferreira, Osania Emerenciano [UNESP]; Montijo, Nayara Abrão [UNESP]; Martins, Eduardo da Silva; Mutton, Márcia Justino Rossini [UNESP] (Academic Journals, 2015)
A thermotolerant strain of Rhizopus oryzae was grown in three agro-industrial by-products: brewers’ rice, corn grits and wheat bran. Different substrates, cultivation time, moisture content, additional nitrogen sources, pH and temperature of incubation were evaluated aiming to optimize growing conditions. The highest enzymatic activity was observed after 24 h of cultivation using wheat bran as substrate with the following salt solutions: NH4NO3, MgSO4.7H2O and (NH4)2SO4 0.1% at temperature of 35°C. It was observed that changes in the pH range 4.0-6.0 did not significantly affect α-amylase activity. The optimum operation conditions were 75°C and pH 4.5. The enzymes remained stable at 75°C in the absence of substrate for 25 min.
Keywords: Starch hydrolisys; Fermentation parameters; Amylolityc enzyme